PROJECT EDUCATION AS A WORK WITH INFORMATION - Georgii L. Il'yin (Высшее образование в России)
The article addresses the changes and trends in modern education such as the dominance of training over education, detachment of training from education and the emergence of differences between knowledge and information. The author substantiates the necessity of a new understanding of education, based on continuity and puts forward the idea of personal projective education. The main goal of education is the ability to work with information, which is treated as a semi-finished product from which the right knowledge should be drawn. The author also spells out the principles of working with information and defines the concept of personal truth, in contrast to objective truth, - the result of working with information.